2022
DOI: 10.1021/acsami.1c17859
|View full text |Cite
|
Sign up to set email alerts
|

Column Agglutination Assay Using Polystyrene Microbeads for Rapid Detection of Antibodies against SARS-CoV-2

Abstract: Rapid serology platforms are essential in disease pandemics for a variety of applications, including epidemiological surveillance, contact tracing, vaccination monitoring, and primary diagnosis in resource-limited areas. Laboratory-based enzymelinked immunosorbent assay (ELISA) platforms are inherently multistep processes that require trained personnel and are of relatively limited throughput. As an alternative, agglutination-based systems have been developed; however, they rely on donor red blood cells and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Serological assays that have been developed for COVID-19 detection include techniques based on enzyme-linked immunosorbent assays (ELISA), chemiluminescent assays, lateral flow assays, and others. 4 6 , 10 , 12 16 However, these techniques either suffer from low sensitivity when quantifying a low abundance of biomarkers, especially at a high specificity, 5 , 9 , 12 , 15 , 16 or are unable to differentiate immunoglobulin-G (IgG) specific to SARS-CoV-2 from other novel coronaviruses. 14 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Serological assays that have been developed for COVID-19 detection include techniques based on enzyme-linked immunosorbent assays (ELISA), chemiluminescent assays, lateral flow assays, and others. 4 6 , 10 , 12 16 However, these techniques either suffer from low sensitivity when quantifying a low abundance of biomarkers, especially at a high specificity, 5 , 9 , 12 , 15 , 16 or are unable to differentiate immunoglobulin-G (IgG) specific to SARS-CoV-2 from other novel coronaviruses. 14 …”
Section: Introductionmentioning
confidence: 99%
“…A highly specific serology antibody assay for COVID-19 must include a receptor molecule that is a subset of the SARS-CoV-2 spike protein and a detection analyte that would be SARS-CoV-2 neutralizing antibody (IgG). 10 , 15 , 26 , 27 Recent works by Ng and co-workers showed that around 18 peptides in length of the spike protein segments, called linear epitopes, have a higher binding affinity toward SARS-CoV-2 neutralizing antibody IgG, suggesting a further improvement in specificity. 9 , 26 The authors reported a gold nanoparticle-based colorimetric assay to detect IgG from clinical samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aggregation of particles via specific interactions between complementary biological components has gained increasing attention in medical diagnosis due to its simplicity, practicality, and low cost [7][8][9][10][11][12][13][14][15][16]. Traditionally, agglutination assays based on polystyrene nanoand microspheres, well-known as the latex agglutination test, have been extensively used.…”
Section: Introductionmentioning
confidence: 99%